Density-dependent effect of allelopathy on germination and seedling emergence in two Ipomoea species - Aguilar-Franco, Zoila Mercedes; Flores-Palacios, Alejandro; Flores-Morales, Alejandro; Perea-Arango, Irene; Arellano-García, José de Jesús; Valencia-Díaz, Susana (Revista chilena de historia natural, 2019)
Background Density in inter and intraspecific plant-plant interactions affects the action modes of allelopathy (autotoxicity, negative and positive allelopathy). Some seeds exude compounds that inhibit the germination of others. Ipomoea murucoides and I. pauciflora are sympatric tree species that form patches at the local scale where one or the other dominates, possibly due to allelopathy in the seeds. The objective of this study was to determine the possible density-dependence of the allelopathic effect among seeds of these species through the measure of seed germination and seedling emergence. Methods In both species, allelopathy was measured as: a) germination in mixed sowing of both species at different proportions, b) germination in single-species trials at different densities after adding seed extracts of both species, and c) seedling emergence in seed mixtures of both species sown at different proportions beneath canopies of the two Ipomoea species. Results Seed germination of I. murucoides was increased by the presence of I. pauciflora and diminished at higher densities of its own seeds; however, seed germination of I. pauciflora was not affected by the presence of I . murucoides seeds. The addition of extracts (either from conspecifics or congeneric) diminished the germination of both species and at higher seed densities the germination was lower. Seedling emergence did not depend on the species under which the seeds were sown nor on the density of the seeds. Conclusions The germination experiments evidenced positive allelopathy and/or autotoxicity, while there was no evidence of allelopathic effects in seedling emergence. The allelopathic activity is reported in the seeds of these species for the first time.